Active Edge‐Site‐Rich Carbon Nanocatalysts with Enhanced Electron Transfer for Efficient Electrochemical Hydrogen Peroxide Production. Issue 4 (21st December 2018) - Sa, Young Jin; Kim, Jae Hyung; Joo, Sang Hoon
Abstract: A highly efficient, metal‐free carbon nanocatalyst is presented that possesses abundant active, oxygenated graphitic edge sites. The edge site‐rich nanocarbon catalyst exhibits about 28 times higher activity for H2 O2 production than a basal plane‐rich carbon nanotube with a H2 O2 selectivity over 90 %. The oxidative treatment further promotes the H2 O2 generation activity to reach close to the thermodynamic limit. The optimized nanocarbon catalyst shows a very high H2 O2 production activity, surpassing previously reported catalysts in alkaline media. Moreover, it can stably produce H2 O2 for 16 h with Faradaic efficiency reaching 99 % and accumulated H2 O2 concentration of 24±2 mm . Importantly, we find that the heterogeneous electron transfer kinetics of the carbon‐based catalyst is closely related to the electrocatalytic activity, suggesting that first outer‐sphere electron transfer to O2 is an important step governing the H2 O2 production rate. Abstract : A carbon nanocatalyst that is rich in active edge sites is developed, which shows high activity and selectivity for electrochemical H2 O2 production. The H2 O2 production activity surpasses previously reported catalysts in alkaline media, and can sustainably produce H2 O2 for 16 h with Faradaic efficiency reaching 99 %. The superior activity can be correlated to the enhanced electron transfer capabilities of the (oxygenated) edge‐rich carbon.